DEMETER: an original reasoning to assess and control the loss of agricultural land related to the urban sprawl. - Patrick Le Gouee (European Regional Science Association (ERSA), 2010)
In the prolongation of the research actions relating to interregional program PSDR GO DYTEFORT, we have developed the program DÉMÉTER. This one is articulated around three objectives. At the level of the department of Calvados (5500 km²) and over one recent period (1998-2006), it is a question (1) of quantifying agricultural areas which have been lost by the urban sprawl, (2) to identify for each of the 705 communes of the Calvados the sectors to preserve urban sprawl when those are characterized by soils with an agronomic strong potential, (3) to take the measurement of the environmental and economic consequences induced by the artificialisation of the soil resource. A short presentation of the results of this study shows that between 1998 and 2006, the Calvados has recorded a loss of agricultural areas related to the urban sprawl of about 5100 hectares. That represents the equivalent of the area of 7 communes of the department or 7285 football fields. 45% of urbanized areas have concerned soils with high agronomic potentiality. 16% of urbanized areas (850 ha) have involved the appearance of a high erosive risk. The cereal production loss in 2006 compared to 1998 has corresponded about 153,000 quintals and about 22,000 tons of dry matter for the fodder productions. The restitution of the study near the territory agencies has led (1) on an awakening of the policy-makers to quickly mitigate the environmental and economic consequences of the urban sprawl, (2) to a wish to use the data of our study as a significant tool for the sustainable development in rural areas, (3) on the need for reinforcing the partnerships between the structures of research and the policy-makers.
Keywords: 330; DEMETER; urban sprawl; agricultural land; sustainable development